In Vivo and In Vitro Matured Oocytes From Mice of Advanced Reproductive Age Exhibit Alternative Splicing Processes for Mitochondrial Oxidative Phosphorylation - Qin, Hao; Qu, Yi; Li, Rong; Qiao, Jie (Frontiers in Endocrinology, 2022)
The mean age of women seeking infertility treatment has gradually increased over recent years. This has coincided with the emergence of in vitro maturation (IVM), a method used in assisted reproductive technology for patients with special requirements. However, when compared with conventional in vitro fertilization, IVM is associated with poor embryonic development potential and low live birth rates, thus limiting the widespread application of this technique. In this study, we performed RNA-sequencing transcriptomic assays and identified a total of 2,627 significant differentially expressed genes (DEGs) between IVM oocytes and in vivo matured oocytes from mice of advanced reproductive age. Next, Kyoto Encyclopedia of Genes and Genomes pathway analysis was used to identify the potential functions of the DEGs. The most significantly enriched pathway was oxidative phosphorylation (OXPHOS). In addition, we constructed a protein-protein interaction network to identify key genes and determined that most of the hub genes were mtDNA-encoded subunits of respiratory chain complex I. Antioxidant supplementation lead to an increase in ATP production and reduced the gene expression profile of the OXPHOS pathway in the IVM group. Moreover, alternative splicing (AS) events were identified during in vivo or in vitro oocyte maturation; data showed that skipped exons were the most frequent type of AS event. A number of genes associated with the OXPHOS pathway exhibited alterations in AS events, including Ndufa7, Ndufs7, Cox6a2, Ndufs5, Ndufb1, and Uqcrh. Furthermore, the process of IVO promoted the skipping of exon 2 in Ndufa7 and exon 3 in Ndufs7 compared with the IVM oocytes, as determined by semi−quantitative RT−PCR. Collectively, these findings provide potential new therapeutic targets for improving IVM of aged women who undergo infertility treatment.